La grammaire en première personne (I) - Pierre Cotte (Anglophonia)
A distinction between a first-person perspective and a third-person one is common in philosophical discussions of consciousness. As it is generally understood, the first-person perspective, informally, relates to a person’s ‘felt’ experience of situations, while a third-person perspective is an external look at things. This paper considers extending the distinction to the semantic study of grammar and is the first of a series on the subject of grammar in a first-person perspective. The first part of the paper is an informal discussion of the distinction and its relation to language. The second part is about the well-known derivation of purpose markers from allative markers, with reference to the polysemy of English ‘to’. It is shown that varying the perspective under study changes the analysis. The derivation is construed as metaphorical if it seen in a third-person perspective (this being the received interpretation) but it is construed as involving synecdoche when seen in a first-person perspective. It appears that the two constructions are not contradictory.